2022
DOI: 10.1016/j.xjidi.2021.100066
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of Keratinocyte Mitogens: Implications for Hyperproliferation in Psoriasis and Atopic Dermatitis

Abstract: Psoriasis and atopic dermatitis are chronic inflammatory skin diseases characterized by keratinocyte (KC) hyperproliferation and epidermal acanthosis (hyperplasia). The milieu of disease-associated cytokines and soluble factors is considered a mitogenic factor; however, pinpointing the exact mitogens in this complex microenvironment is challenging. We employed organotypic human epidermal equivalents, faithfully mimicking native epidermal proliferation and stratification, to evaluate the proliferative effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 116 publications
0
11
0
Order By: Relevance
“…Dysfunction of epithelial layer is involved in various disorders, such as inflammatory and allergic diseases. [7][8][9][10][11][12][13][14][15][16] Thus, chemical mediators and their receptors that orchestrate epithelial homeostasis have received great attention as potential therapeutic targets for epithelial diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Dysfunction of epithelial layer is involved in various disorders, such as inflammatory and allergic diseases. [7][8][9][10][11][12][13][14][15][16] Thus, chemical mediators and their receptors that orchestrate epithelial homeostasis have received great attention as potential therapeutic targets for epithelial diseases.…”
Section: Introductionmentioning
confidence: 99%
“…After examining EIS in epidermal homeostasis we aimed to study the relevance of EIS in the context of disturbed homeostasis and to deepen our investigation into the correlation between EIS diff , epidermal thickness and terminal differentiation. Therefore, HEEs from normal human keratinocytes (NHEKs) were stimulated with single cytokines (interleukin–(IL–) 17A or IL–22) or cytokine mixes (IL–17A + IL–22 and IL–4 + IL–13) to mimic a pro–inflammatory milieu that is known to affect keratinocyte proliferation (IL–4, IL–13, IL–17A), the cell volume (IL–22), and terminal differentiation (all cytokines) (Niehues et al . 2021) (Figure 4a).…”
Section: Resultsmentioning
confidence: 99%
“…Epidermal hyperplasia is a histological hallmark promoted by various growth factors and cytokines such as keratinocyte growth factor (KGF), IL-4, IL-13, IL-17A, IL-22, and IL-24 in AD [ 103 , 104 ]. We found that ghrelin suppresses epidermal hyperplasia probably due to inhibition of expression of IL-4, IL-13, and IL-22 genes by ghrelin in DNFB-induced AD-like mouse skin, implying anti-proliferation activity of ghrelin ( Supplementary Figure S1 ).…”
Section: Discussionmentioning
confidence: 99%